A Numerical Investigation Into the Performance and Aerodynamics of a Vertical Axis Wind Turbine - Danao, Louis Angelo (Philippine Engineering Journal, 2021)
Numerical simulations were carried out to investigate the performance of a wind tunnel scale vertical axis wind turbine (VAWT). Steady wind simulations at U=7m/s have shown that at the low λ range, there is a distinct negative trough in the power coefficient (CP) that is drag-dominated and consistent to experimental results. Minimum CP is -0.04 at λ = 2 while maximum CP is 0.33 at λ * = 4.5. A closer inspection of two λ’s reveals that λ-2, the blades experience stalled flow initially from a separation bubble forming at θ = 60⁰ with subsequent shedding of vortices. Reattachment occurs very much delayed beyond halfway of the rotation. The same delayed reattachment is observed in the second quadrant of rotation with the deepest stall seen at θ =130⁰. High values of positive blade torque T b reaching 1N m are predicted in the upwind while most of the downwind region θ = 190⁰ to θ = 340⁰ also produce positive performance that contribute to the overall positive CP of just below 0.3. Keywords: computational fluid dynamics, vertical axis wind turbine, aerodynamics